Hermaphroditism: what's not to like? - Evelyn Korn; Lena Edlund (Philipps-Universität Marburg, Fachbereich Wirtschaftswissenschaften, 2006)
Male and female social roles are largely predicated on the fact that male and female reproductive functions are separated in different individuals. This paper asks why gonochorism rather than hermaphroditism, is the rule among vertebrates. We argue that hermaphroditism may be unstable in the face of heterogeneity. Building on the Bateman principle access to eggs, not sperm, limits reproductive success and in line with Trivers-Willard, we show that low quality individuals will prefer to be all female. Moreover, without secondary sexual differentiation (SSD), males cannot exist in equilibrium. With sufficient SSD, however, males may outcompete hermaphrodites. As a result, while hermaphrodites may coexist with males and females, they mate among themselves only. The lack of interbreeding between hermaphrodites and gonochorists may form the basis for further speciation. Furthermore, while hermaphrodites strive to mate their male function and preserve their female function, equilibrium hermaphroditic mating is reciprocal. Reciprocal mating, in turn, makes hermaphrodites vulnerable to male-to-male violence, a form of SSD that may have contributed to the rarity of hermaphroditism.
Keywords: 330